ANALYSIS AND DECREASING OF THE SHRINKAGE AND WARPAGE OF INJECTION MOLDED PLASTIC PART - HREBENIUK, BOGDAN; MYLKO, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The production of parts and components from plastic materials by injection molding in a mold is the most extensive and most productive method of production. The current phase of development of science and technology is expected to reach a high level of availability of products and parts made from plastic materials. Improving product quality in conditions of high competition is a necessary requirement for staying competitive in the market. Defects that arise during the injection molding process of plastic parts negatively affect product quality. Mitigating warpage begins with addressing variances in temperature, materials, and improper tooling. You should work early with your manufacturer, as it’s during the design phase that troubleshooting defects can have the lowest impact on your bottom line. During the prototyping phase, an engineer will ensure the proper materials, tool design, processes, and machine settings will work in conjunction to prevent warpage. However, should warpage occur despite the safeguards, engineers will inspect where and how much warpage is present and its effects on the part to isolate the culprit. Achieving high product quality is impossible without the use of engineering analysis systems. Modern software tools make it possible to simulate the injection molding process and predict potential molding defects. Iterating designs through manual or automated workflows enable engineers to change processing conditions or part design to identify a combination that produces an acceptable part. Moldflow’s automated optimization analyses, provide straightforward feedback on the influence of design, material, and process changes toward part warpage. Reducing shrinkage and warpage defects requires a comprehensive approach to the injection molding process: understanding material properties, designing molds, and setting process parameters. In this work, the injection molding process of a plastic part was simulated, and results for the part’s shrinkage and warpage were obtained. A solution was also proposed that helped reduce these defects. Thus, the analysis reveals new possibilities for predicting possible defects in injection molding, methods and approaches to eliminate defects at the primary stages, which today is widely accepted approaches to the injection molding process that will ensure a high level of quality of products and parts.
Keywords: Injection molding; SolidWorks Plastics; shrinkage; warpage; analysis of injection molding